PENERAPAN E-COMMERCE PADA KARANG TARUNA KOMPLEK NUSA HIJAU - Anggreini, Novita Lestari; Ekawati, Nia; Tresnawati, Shandy (PUAN INDONESIA, 2024)
The purpose of this community service is to increase community awareness of technology in the field of e-commerce and educate about how to utilize it through entrepreneurship. Nusa Hijau Complex has a Youth Organization which consists of junior high school and high school students. But even though the average Karang Taruna member is a school student, they always hold social activities such as sharing happiness with orphans, working together to clean up the complex environment, and holding studies on educational matters. The understanding of e-commerce in the community is certainly still limited, so from this the service team wants to provide enlightenment from the application of e-commerce itself. The target of the current service team is Karang Taruna Komplek Nusa Hijau, this service activity is well received by the service participants, so that the application of e-commerce can be implemented properly.